Need Assessment Study For Wheelchair Users In Gujarat, India - Harshul Brahmbhatt (Iranian Rehabilitation Journal, 2024)
Objectives: This is a need assessment study conducted on wheelchair users with limited locomotion ability in the legs in the Ahmedabad urban region in India. The results describe the unmet needs in the indoor and outdoor settings. Even though India is a large country with huge diversity in local climate and terrain and big socio-economic disparity, need assessment studies for assistive technology across various socio-economic or with region specificity are extremely scarce. Accordingly, this study aims to understand the needs and requirements of mobility assistive technology users that are not met by their current devices. Methods: Data from 69 participants having physical disabilities were collected through interviews and 6 of the participants were video-tapped to observe their daily routine. Meanwhile, a qualitative analysis of the collected data was carried out. Results: The analysis highlights problems of participants, such as working in the kitchen, inability to perform everyday indoor tasks, inaccessibility of toilets and public transport, etc. Discussion: A mixture of qualitative and quantitative data analysis showed that the major features that the Indian wheelchair users wanted were the ability to adjust the height of the chair, the ability to reach objects without too much maneuvering of the wheelchair, ease of transfer from wheelchair to toilet seat and back and also meet outdoor needs. Hence, a wheelchair that can be used in both indoor and outdoor settings is one of the most imminent needs for such wheelchair users.